Physiotherapy in peripheral facial palsy or bell's palsy - Rocha, Elisangela da Silva; Silva, Fabiana Rosa da; Almeida, Fernanda Barbosa de; Andrade, Gláucia de Jesus; Freitas, Iohana Nunes de; Barros, Izabela de Souza; Pereira, Leidiana Avila; Rodrigues, Laura de moura; Cavalcante, Fabrício Vieira (JRG Journal of Academic Studies, 2024)
Peripheral facial paralysis (PFP) or Bell's palsy (BP) is determined by facial weakness, caused by acute paralysis of the seventh cranial nerve, without detectable cause, which controls the muscles of the face. The objective of this study is to analyze how physical therapists who are in professional practice, in relation to people with peripheral facial paralysis, with the aim of improving the functional, psychosocial and physical development of people with this paralysis. This study will be carried out through a literature review, with the purpose of examining the scientific evidence related to physical therapy in peripheral facial paralysis or Bell's palsy. The literature review allows a systematic and comprehensive theoretical survey, integrating several sources to consolidate the understanding about the topic under discussion. The results of the study were categorized and planned based on the main clinical results observed, such as the recovery of facial symmetry, the improvement of muscle functionality and the reduction of complications, such as synkinesia. The inclusion criteria used were articles published between January 2018 and December 2023, covering the topic addressed, with a publication date within the standards, with 11 (eleven) articles being used. Finally, physiotherapy plays a fundamental role in the treatment of Peripheral Facial Paralysis, also known as Bell's Palsy. It is essential for the patient's recovery, offering benefits that go beyond the physical aspect, including psychological support and help in social reintegration.